EZH2 Promotes Expansion of Breast Tumor Initiating Cells through Activation of RAF1-β-Catenin Signaling - Chang, Chun-Ju; Yang, Jer-Yen; Xia, Weiya; Chen, Chun-Te; Xie, Xiaoming; Chao, Chi-Hong; Woodward, Wendy A.; Hsu, Jung-Mao; Hortobagyi, Gabriel N.; Hung, Mien-Chie (Cancer cell, 2011)
It has been proposed that an aggressive secondary cancer stem cell population arises from a primary cancer stem cell population through acquisition of additional genetic mutations and drives cancer progression. Overexpression of Polycomb protein EZH2, essential in stem cell self-renewal, has been linked to breast cancer progression. However, critical mechanism linking increased EZH2 expression to BTIC (breast tumor initiating cell) regulation and cancer progression remains unclear. Here, we identify a mechanism in which EZH2 expression-mediated downregulation of DNA damage repair leads to accumulation of recurrent RAF1 gene amplification in BTICs, which activates p-ERK-β-catenin signaling to promote BTIC expansion. We further reveal that AZD6244, a clinical trial drug that inhibits RAF1-ERK signaling, could prevent breast cancer progression by eliminating BTICs. ► Increased EZH2 expression in BTICs enhances BTIC survival and proliferation ► EZH2-amplified RAF1-β-catenin signaling promotes BTIC expansion ► Hypoxic microenvironment promotes BTICs through upregulating EZH2 expression ► AZD6244 suppresses BTICs by inhibiting activated RAF1-ERK-β-catenin signaling